Pythagorean Theorem Concept Image in Junior High School: An Analysis in The Online-Based Learning - Mohamad Gilar Jatisunda; Vici Suciawati; Dede Salim Nahdi (Universitas Syiah Kuala, 2021)
The concept image comprises all the cognitive structures in an individual's mind connected with a specific notion. However, if the learning situation is not relevant to help students construct knowledge and provide meaningful experiences, it will affect their concept image. This study aims to examine the concept of the image of the Pythagorean theorem during online-based learning. The research is a qualitative approach, and the method is phenomenological to understand the meaning for the participants of their concept image. Initially, this study enrolled 66 students. Two students were selected as research subjects and acted as resource persons to provide adequate contextualization based on students who answered right and wrong. Data collection combines data from the outcomes of testing the Pythagorean theorem test, interviews, and literature studies. The data analysis technique employed is Interpretative Phenomenological Analysis (IPA). There are six categories of student concept image. Based on in-depth interviews with two students who answered correctly and incorrectly, students were given inconsistent meanings of the Pythagorean theorem due to the learning situation to improve students' understanding of the subject.